The effect of Geometrical parameters on heat transfer coefficient in helical double tube exchangers - Seyed Faramarz Ranjbar; Mir Hatef Seyyedvalilu (Journal of Heat and Mass Transfer Research, 2014)
Helical coil heat exchangers are widely used in industrial applications ranging fromcryogenic processes, air-conditioning, and nuclear reactors to waste heat recovery due totheir compact size and high heat transfer coefficient. In this kind of heat exchangers, flowand heat transfer are complicated. This paper reports a numerical investigation of theinfluence of different parameters such as coil radius, coil pitch and diameter of tubeon the characteristics of heat transfer in helical double tube heat exchangers usingthe well-known Fluent CFD software. Modeling of the study was implemented based onprinciples of heat transfer, fluid mechanics, and thermodynamics. By imposing boundaryconditions and selecting of an appropriate grid, whereby the results are independent ofmeshing, the obtained results were compared and validated with existing experimentalresults in the open literature. The results indicate that heat transfer augments by increasingof the inner Dean number, inner tube diameter, curvature ratio, and by the reduction of thepitch of the heat exchanger coil.